Professional Judgement in Ethical Decision Making: Dialogue and Relationship - Lehr, Ron; Sumarah, John (Canadian Journal of Counselling and Psychotherapy, 2007)
This article examines the role of professional judgement in the ethical decision-making process. Drawing on the personalist philosophy of John MacMurray, and the CCA Code of Ethics and Standards of Practice, the authors propose that a social constructivist approach involving dialogue and relationship complement the current internal psychologically based ethical decision-making models. An examination of the literature on ethical decision-making is followed by an overview of MacMurray's philosophy and its ethical implications for counsellors.